2021
DOI: 10.21203/rs.3.rs-380527/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thirty years of genetic progress combined with seed ethylene priming improved drought resistance of wheat through long-term drought stress memory

Abstract: Knowledge of short-term physiological adaption of wheat to soil water deficit is well understood, but little is known about seed ethylene priming effect on long-term drought stress memory of dryland winter wheat. The 42 leading and new cultivars released between 1992 to 2017 were subjected to drought (45% Field water-holding capacity), and well-watered (75% Field water-holding capacity) conditions aim to screen cultivars with contrasting drought resistance and grain yield. Seeds primed with ethylene were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Drought at tillering might disturb the hormones regulating tillering pathway, roots functioning and leaf physiological process (Bacher et al 2022;Yang et al 2022). Abid et al (2016) and Yang et al (2021) investigated the effects of drought stress on wheat tillering and found that moderate drought stress results in a reduction of the number of tillers per plant, while severe drought stress causes a significant reduction in both tiller number and size. The unaffected wheat tillers under mild drought imply that wheat plants tend to conserve moisture rather than using maximum field capacity.…”
Section: Drought Stress During Tillering Reduces Growth and Yield Of ...mentioning
confidence: 99%
“…Drought at tillering might disturb the hormones regulating tillering pathway, roots functioning and leaf physiological process (Bacher et al 2022;Yang et al 2022). Abid et al (2016) and Yang et al (2021) investigated the effects of drought stress on wheat tillering and found that moderate drought stress results in a reduction of the number of tillers per plant, while severe drought stress causes a significant reduction in both tiller number and size. The unaffected wheat tillers under mild drought imply that wheat plants tend to conserve moisture rather than using maximum field capacity.…”
Section: Drought Stress During Tillering Reduces Growth and Yield Of ...mentioning
confidence: 99%